已知a+b+c=a^2+b^2+c^2=2,求证a(1-a)^2=b(1-b)^2=c(1-c)^2

我初一,得让我看懂,否则不选,谢谢合作。
2025-02-26 21:58:28
推荐回答(2个)
回答1:

证明 先计算 bc+ca+ab=[(a+b+c)^2-(a^2+b^2+c^2)]/2=1
设f(x)=x(1-x)^2,只需证明:f(a)=f(b)=f(c) 即可.
注意恒等式运算
(x-a)*(x-b)*(x-c)=x^3-(a+b+c)x^2+( bc+ca+ab)x-abc=x^3-2x^2+x-abc
所以得
f(x)=(x-a)*(x-b)*(x-c)+abc (1)
令x=a,b,c依次得:f(a)=f(b)=f(c) .
从而 a(1-a)^2=b(1-b)^2=c(1-c)^2=abc。

回答2:

a+b+c=a^2+b^2+c^2=2

2*(+b+c)=a^2+b^2+c^2+2

a^2-2a+b^2-2b+c^2-2c+2=0

(a-1)^2+(b-1)^2+c^2=0
因为平方>=0
所以
a=1,b=1,c=0
所以
a(1-a)^2=0
b(1-b)^2=0
c(1-c)^2=0

a(1-a)^2=b(1-b)^2=c(1-c)^2